Effect of aqua exercise on recovery of lower limb muscles after downhill running - Takahashi, J.; Ishihara, K.; Aoki, J. (Journal of Sports Sciences, 2006)
The aim of the present study was to examine how the recovery of physiological functioning of the leg muscles after high-intensity eccentric exercise such as downhill running could be promoted by aqua exercise for a period until the damaged muscle had recovered almost completely. Ten male long-distance runners were divided equally into an aqua exercise group and a control group. From the first day (Day 0) to the fourth day (Day 3), the participants completed a questionnaire on muscle soreness, and serum creatine kinase activity, muscle power, flexibility, whole-body reaction time and muscle stiffness were measured. After measurements on Day 0, the participants performed downhill running (three 5 min runs with a 5 min rest interval at -10%, 335.7 ± 6.1 m · min-1). The aqua exercise group performed walking, jogging and jumping in water on three successive days following the downhill running on Day 0 for 30 min each day. Muscle power was reduced on Day 1 in the control group (P < 0.05). Muscle soreness in the calf on Day 3 was greater in the control group than that in the aqua exercise group (P < 0.05). In the aqua exercise group, muscle stiffness in the calf was less than that in the control group over 4 days (time main effect: P < 0.05; group × time interaction: P < 0.05). We conclude that aqua exercise promoted physiological functioning of the muscles in the legs after high-intensity downhill running for a period until the damaged muscles had recovered almost completely.